Optimasi Dosis Pupuk Anorganik dan Pupuk Kandang Ayam pada Budidaya Tomat Hibrida (Lycopersicon esculentum Mill. L.) - Haveel Luthfyrakhman; Anas D. Susila (Departemen Agronomi dan Hortikultura, 2013)
The objective of this research was study the effect of fertilizer and manure on growth and productivity of hybrid tomato(Lycopersicon esculentum Mill. L). This research conduced at Pasir Sarongge experimental field University Farm, Bogor Agricultural University, Cipanas, from February to July 2011. The experimental design used was Completely Randomized Block Design, with two factors and three replications. The first factor was manure dosages which were 0, 10, 20, and 30 ton ha-1. The second factor was fertilizer dosages which were 0%, 75%, and 150% of recommended dosage. Recommended dosage use was 100 kg ha-1 N, 100 kg ha-1 P2O5, and 50 kg ha-1 K2O, from Ministry of Agriculture. Plant height showed quadratic response to manure at 2 and 4 week after transplanted (WAT), then linier at 6 WAT. To the fertilizer, plant height showed no response at 2 WAT and has not shown linier response at 4 and 6 WAT. Interaction between manure and fertilizer was significant at 8 WAT. Manure gave linier effect to number of leaves at 2, 4, and 8 WAT but not significant at 6 WAT. Fertilizer gave no significant effect to number of leaves. Manure gave quadratic effect where as fertilizer gave linier effect to fruit weight per plot, fruit weight per hectare estimated, and relative yield. Optimum manure dose obtained from this research was 24.375 ton ha-1. Maximum fruit weight per plot was 17.41 kg. Estimated maximum fruit weight per hectare was 22.79 ton ha-1. Manure gave linier effect to fruit weight per plot of grade A and B. Fruit weight per plot of grade C, fruit diameter, and average fruit weight were not affected by manure or fertilizer given.Keywords : tomatoes, fertilizer, chicken manure, Lycopersicon esculentum